Imagining a better world: assessing the immediate and delayed effects of imagined contact on attitudes toward refugees in elementary school - Vrdoljak, Antonija; Čorkalo Biruški, Dinka; Stanković, Nikolina; Fasel, Rachel; Butera, Fabrizio; Jelić, Margareta (Frontiers in Psychology, 2024)
Introduction Preparing host-society children for contact with refugees coming into their classes poses a new and important challenge for countries with little prior experience in integration. Imagined contact is a prejudice-reduction intervention that can be particularly useful in this context. However, its long-term effects and potential age-related variations in its efficacy among primary school children remain understudied. Methods This study investigated the short-term and long-term effects of an imagined contact school intervention on the change in attitudes and contact intentions of 1,544 children aged 7–15. Of these, 827 participated in a four-session-long intervention delivered by their teachers within their regular classes, while 717 served as a comparison group. Short-term effects were assessed approximately one week after the last intervention session, with long-term effects evaluated around two and a half months later. Results Our findings indicate that the imagined contact intervention instigates positive changes in intergroup attitudes and contact intentions in both the short term and long term, but only for the children in the lower grades of primary school. Discussion While the durability of these effects among younger participants holds promise for future use of imagined contact in schools, we also scrutinize potential developmental and methodological explanations of the absence of expected intervention effects among older children.